Pengetahuan Sikap Dan Masa Kerja Dengan Tindakan Perawat Dalam Pembuangan Sampah Medis Benda Tajam Di RS PKU Muhammadiyah Yogyakarta - Gailea, Anggriani Ahmad; Maulana, Muchsin (Universitas Ahmad Dahlan, 2025)
Improper disposal of sharp medical waste is a critical environmental and occupational health issue, contributing to the spread of infectious diseases and increasing the risk of injury among healthcare workers. This study investigates the relationship between nurses’ knowledge, attitudes, and length of service with their practices in disposing of sharp medical waste at RS PKU Muhammadiyah, Indonesia. A cross-sectional analytic survey was conducted in April 2023 involving 71 contract nurses selected through random sampling. Data analysis included univariate and bivariate methods using the chi-square test. Findings revealed a statistically significant association between knowledge and proper disposal practices (p = 0.013), while no significant relationships were found for attitude (p = 0.838) or length of service (p = 0.786). These results highlight the pivotal role of knowledge in promoting safe and environmentally responsible medical waste management. Strengthening continuous education and training programs for healthcare personnel is essential to improving waste handling practices and minimizing environmental and health risks. Keywords: sharp medical waste, healthcare workers, waste disposal, knowledge